Policing places with drug problems - Green, Lorraine A. (Drugs, health, and social policy series, 1996)
Introduction -- The traditional approach -- Policing places and problems -- SMART approach -- Civil remedies for crime control purposes -- What follows -- Places, crimes and prevention perspectives -- Places and crimes -- Crime prevention perspectives -- Side effects of place control programs -- Summary -- Policing places with drug problems : Oakland's SMART approach -- The Oakland site -- The SMART program -- Program implementation -- Summary -- The SMART program impact -- City-wide trends in drug activity -- City-wide and SMART site trends -- SMART impact on place appearances -- Spatial, social and prevention influences -- Target places and intervention dosage -- Summary -- Displacement and diffusion effects -- Prior research -- Measuring displacement and diffusion effects -- Change in catchment areas -- People contacted in catchment areas -- Offender movement patterns -- Summary -- Conclusions -- What changes a place? -- The challenges of policing places with drug problems -- Successfully policing places with drug problems -- Final word